Characters of the New Testament as culturemes in Spanish language - Жук, Марина Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the characters of the New Testament as culturemes in Spanish. Guided by viability, figurative usage, phraseology motivation, frequency of usage in movies, songs, advertising, comic books and cartoons, in text allusions, jokes, and other variations we have identified seven characters that are found in the Gospels as culturemes in Spanish language. These culturemes are illustrated by examples of their usage, as well as the biblical texts that became a foundation in their formation.